2008
DOI: 10.1080/00952990802308213
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam for the Treatment of Co-Occurring Alcohol Dependence and Anxiety: Case Series and Review

Abstract: Objectives-Alcohol dependence is frequently associated with anxiety disorders. The exact nature of the relationship between alcohol dependence and anxiety disorders is unknown, but emerging evidence suggests that in a majority of cases, the anxiety disorder is independent of the alcohol use disorder. There is pre-clinical and clinical evidence that levetiracetam, a newer generation anticonvulsant medication, may be efficacious in the treatment of co-occurring alcohol use and anxiety disorders. Methods-In an op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
10
0
2
Order By: Relevance
“…There is also preclinical evidence that levetiracetam reduces alcohol consumption by altering β-endorphin release in alcohol-preferring rats [75]. Levetiracetam may also have efficacy in alcohol-dependent subjects with co-occurring psychiatric disorders; in three patients with co-morbid alcohol dependence and anxiety disorder(s), 8 weeks of levetiracetam (up to 3000 mg/day) decreased both alcohol consumption and anxiety [76]. …”
Section: Anticonvulsants For the Treatment Of Harmful Drinking Pattmentioning
confidence: 99%
“…There is also preclinical evidence that levetiracetam reduces alcohol consumption by altering β-endorphin release in alcohol-preferring rats [75]. Levetiracetam may also have efficacy in alcohol-dependent subjects with co-occurring psychiatric disorders; in three patients with co-morbid alcohol dependence and anxiety disorder(s), 8 weeks of levetiracetam (up to 3000 mg/day) decreased both alcohol consumption and anxiety [76]. …”
Section: Anticonvulsants For the Treatment Of Harmful Drinking Pattmentioning
confidence: 99%
“…4,5 However, the overall efficacy of acamprosate and naltrexone is still limited. 11,12 For LEV, a favorable safety profile has been demonstrated. 7 In particular, for topiramate, carbamazepine, and valproate, there is some evidence for effects on relapse prevention and reduction of alcohol consumption.…”
mentioning
confidence: 99%
“…The doses of LEV chosen for this study approximate the range of weight-based doses used for seizure prevention in humans, typically 40–80 mg/kg/day. Clinical studies of LEV in alcohol use disorders report using oral doses of 500–4500 mg daily (Mariani and Levin, 2008; Sarid-Segal et al, 2008; Muller et al, 2010; Muller et al, 2011), or 7–64 mg/kg/day in a 70 kg adult. LEV is virtually unaffected by hepatic metabolism (Perucca and Johannessen, 2003; Lacerda et al, 2006), and in the current study a 10mg/kg i.p.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike topiramate, another antiepileptic drug under consideration for maintenance of sobriety in alcoholics (Johnson et al, 2008; Shinn and Greenfield, 2010), LEV is not associated with significant cognitive slowing as determined by objective testing (Gomer et al, 2007) or subjective patient experience (Arif et al, 2009). While several initial reports indicated that LEV may be useful to treat alcohol withdrawal in detoxifying patients (Krebs et al, 2006; Mariani and Levin, 2008; Sarid-Segal et al, 2008; Muller et al, 2010; Richter et al, 2010; Muller et al, 2011), subsequent studies have not yet demonstrated that LEV reduces alcohol intake by self-identified heavy social drinkers or individuals seeking treatment (Fertig et al, 2012; Mitchell et al, 2012; Richter et al, 2012). …”
Section: Introductionmentioning
confidence: 99%